О интерсемиотической передаче комического в аудиодескрипции к советским кинокомедиям - Mocarz-Kleindienst, Maria (Studia Rossica Posnaniensia, 2022)
Audio description (AD) is an additional soundtrack in a film containing concise, verbal information about what is happening on the screen. The language of the AD should be appropriate to the genre of the film lexically and stylistically. This means that the language of AD in film comedies should contain some verbal ‘signals’ of the comic as an aesthetic category. The author of the presented research has attempted to analyse lexical and stylistic means of conveying situational comic and character comic as the two main types of comic, apart from the verbal one expressed directly in the characters’ speech. The material for the research included the following Soviet film comedies: We are from jazz (directed by K. Shakhnazarov, 1983), Autumn marathon (directed by G. Daneliya, 1979), and The twelve chairs (directed by L. Gaidai, 1971). The analysis proved that the verbal track of the AD reflects the most important peripeteia of the characters, and together with them the features of the characters (appearance, character traits), the manner of their behaviour. The set of llinguistic and stylistic means is determined by the type of the comedy.